Crown of roses [compact disc ] - Griffin, Patty, 1964- (PGM ; Thirty Tigers, 2025)
Patty Griffin's new album is a deeply personal and introspective work that explores themes of identity, nature, family, and womanhood. Emerging from a creative drought during the pandemic. Griffin, two-time Grammy winner and Americana Music Association Lifetime Achievement honoree, found herself reevaluating the stories she'd long told herself. The result is an eight-track collection that is both sparse and emotionally rich, blending folk. Americana, and gospel blues.